2023
DOI: 10.1002/adsc.202201002
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Catalyzed Cascade Reaction of Ynamides and 1,3‐Dicarbonyl Compounds for Selective Synthesis of Differently SizedN‐Heterocycles

Abstract: A triphenylphosphine‐ligated cobalt‐catalyzed cyclization manifold with various 1,3‐dicarbonyl compounds and halogenated N‐allyl ynamides was accomplished under alkaline reaction conditions, facilitating the synthesis of differently sized N‐heterocycles. A large array of products was prepared to demonstrate the selective synthesis of N‐heterocycles of different ring sizes (5‐, 6‐, and 7‐membered rings) via cobalt catalysis. The reaction has broad substrate scope and a wide range of functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 91 publications
0
0
0
Order By: Relevance
“…The inherent versatility of this synthetic strategy stimulates the search for new reagents involved in similar transformations. Previous studies have shown that 1,3-dicarbonyl compounds undergo nucleophilic addition reactions with allenes, carbodiimides, and acyclic ketenimines . However, cyclic ketenimines, such as 1,2-didehydroazepines, despite the potential to incorporate the azepine motif into diverse molecular scaffolds and the known method of photoinduced generation of this cyclic heterocumulene, have not been used as substrates in reactions with 1,3-dicarbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The inherent versatility of this synthetic strategy stimulates the search for new reagents involved in similar transformations. Previous studies have shown that 1,3-dicarbonyl compounds undergo nucleophilic addition reactions with allenes, carbodiimides, and acyclic ketenimines . However, cyclic ketenimines, such as 1,2-didehydroazepines, despite the potential to incorporate the azepine motif into diverse molecular scaffolds and the known method of photoinduced generation of this cyclic heterocumulene, have not been used as substrates in reactions with 1,3-dicarbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%